Percutaneous left atrial appendage closure devices: safety, efficacy, and clinical utility - Swaans MJ (Dove Medical Press, 2016)
Martin J Swaans, Lisette IS Wintgens, Arash Alipour,  Benno JWM Rensing, Lucas VA Boersma Department of Cardiology, St. Antonius Hospital, Nieuwegein, the Netherlands Abstract: Atrial fibrillation (AF) is the most common arrhythmia treated in the clinical practice. One of the major complications of AF is a thromboembolic cerebral ischemic event. Up to 20% of all strokes are caused by AF. Thromboembolic cerebral ischemic event in patients with AF occurs due to atrial thrombi, mainly from the left atrial appendage (LAA). Prevention of clot formation with antiplatelet agents and especially oral anticoagulants (vitamin K antagonists or newer oral anticoagulants) has been shown to be effective in reducing the stroke risk in patients with AF but has several drawbacks with (major) bleedings as the most important disadvantage. Therefore, physical elimination of the LAA, which excludes the site of clot formation by surgical or percutaneous techniques, might be a good alternative. In this review, we discuss the safety, efficacy, and clinical utility of the Watchman™ LAA closure device. Keywords: stroke, left atrial appendage, prevention, atrial fibrillation